VD_FINDINFO Jug / 2015 / 121 vom 3. Dezember 2014 - VD Tribunal cantonal (2014)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, EXCÈS DE VITESSE, ÉTAT DE NÉCESSITÉ, EXCUSABILITÉ | 18 CP, 34 al. 1 CP, 42 al. 4 CP, 47 CP, 90 al. 2 LCR